Knowledge of immediate newborn care and management of complications among midwives in Ghana. (June 2023) - Adams, Yenupini Joyce; Ray, Herman E.; Sladek, Lynn; Amason, Janeen
Abstract: Objective: Midwives are instrumental in improving maternal/newborn health outcomes. Since complications after childbirth are leading causes of maternal deaths, midwives' knowledge of how to manage complications and care for the newborn is important. This study assessed midwives' knowledge of immediate newborn care and management of postpartum complications. Design: A cross-sectional descriptive survey design was used. Setting: Four hospitals that provide inpatient maternity services in Tamale, Ghana. Participants: 245 midwives who worked in the four hospitals. Measurements: Data were collected in December 2018 using an electronic survey questionnaire by the Johns Hopkins Program for International Education in Gynecology and Obstetrics, and analyzed using descriptive, bivariate, and multivariate statistics. Findings: About 98% of midwives were female. The mean age of midwives was 31.87 years. The percentage of midwives who responded correctly to questions on newborn care and management of postpartum complications ranged from 29.80% to 89.39%, and 32.17% to 91.43% respectively. Midwives were most knowledgeable about breastfeeding and immediate hemorrhage intervention, and least knowledgeable about cord care, thermal protection, newborn resuscitation, contraindications for vacuum extraction, treating metritis, and performing a cervical repair. Years of experience and age are predictive factors of midwives' knowledge. Conclusion/Implications: There remains the opportunity for continuing education on complication management. Additional training of midwives on newborn resuscitation is recommended.